Microcystin-LR exposure decreased the fetal weight of mice by disturbance of placental development and ROS-mediated endoplasmic reticulum stress in the placenta. (January 2020) - Zhao, Sujuan; Zhong, Shengzheng; Wang, Fang; Wang, Honghui; Xu, Dexiang; Li, Guangyu
Abstract: The placenta is essential for sustaining the growth of the fetus. The aim of this study was to investigate the role of the placenta in MCLR-induced significant reduction in fetal weight, especially the changes in placental structure and function. Pregnant mice were intraperitoneally injected with MCLR (5 or 20 μg/kg) from gestational day (GD) 13 to GD17. The results showed MCLR reduced fetal weight and placenta weight. The histological specimens of the placentas were taken for light and electron microscopy studies. The internal space of blood vessels decreased obviously in the placental labyrinth layer of mice treated with MCLR. After the ultrastructural examination, the edema and intracytoplasmic vacuolization, dilation of the endoplasmic reticulum and corrugation of the nucleus were observed. In addition, maternal MCLR exposure caused a reduction of 11β-hydroxysteroid dehydrogenase type 2 (HSD11B2) expression in placentae, a critical regulator of fetal development. Several genes of placental growth factors, such as Vegfα and Pgf and several genes of nutrient transport pumps, such as Glut1 and Pcft were depressed in placentas of MCLR-treated mice, however nutrient transporters Fatp1 and Snat4 were promoted. Moreover, significant increases in malondialdehyde (MDA) revealed the occurrence of oxidative stress caused by MCLR, which was also verified by remarkable decrease in the glutathione levels, total antioxidant capacity (T-AOC) as well as the activity of antioxidant enzymes. Real-time PCR and western blot analysis revealed that GRP78, CHOP, XBP-1, peIF2α and pIRE1 were remarkable increased in placentas of MCLR-treated mice, indicating that endoplasmic reticulum (ER) stress pathway was activated by MCLR. Furthermore, oxidative stress and ER stress consequently triggered apoptosis which contributed to the impairment of placental development. Collectively, these results suggest maternal MCLR exposure results in reduced fetal body weight, which might be associated with ROS-mediated endoplasmic reticulum stress and impairment in placental structure and function. Graphical abstract: Image 1 Highlights: MCLR reduced placenta weight and led to damage to placental structure. MCLR led to reduced fetal weight, which might be related to disturbance of placental development. Oxidative stress and ER stress maybe the important reasons for placental insufficiency. Abstract : Maternal MCLR results in reduced fetal weight, which might be associated with ROS-mediated endoplasmic reticulum stress and impairment in placental structure and function.